2006
DOI: 10.1111/j.1439-037x.2006.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Inorganic Nutrients for Soil Quality Conservation and Yield of Rainfed Low Land Rice in Sub‐tropical Plateau Region

Abstract: The effect of organic sources of nutrients and inorganic fertilizers, was studied on grain yield of lowland rice and some aspect of soil quality parameters in a field experiment at Agricultural Experimental Farm of Indian Statistical Institute, Giridih, situated at eastern plateau region of India, during consecutive years 1997-2002. Chemical fertilizers and various organic matters were applied to two rice cultivars, Sabita and Subarna. The highest mean grain yield was 3.53 t ha )1 and maximum agronomic efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Manure's advantages as a slow-releasing fertilizer lead to higher DM yield of DL Napiergrass [37]. In the present study, even though fertilizer treatments were not imposed in the last year, higher yield was achieved in the organic fertilizer plots-especially in the LM plot, which achieved the highest DM yield at 22 Mg ha −1 across all plots and years (Figure 1).…”
Section: Discussionmentioning
confidence: 51%
“…Manure's advantages as a slow-releasing fertilizer lead to higher DM yield of DL Napiergrass [37]. In the present study, even though fertilizer treatments were not imposed in the last year, higher yield was achieved in the organic fertilizer plots-especially in the LM plot, which achieved the highest DM yield at 22 Mg ha −1 across all plots and years (Figure 1).…”
Section: Discussionmentioning
confidence: 51%
“…Organic molecules released on decomposition of organic matter form complexes with Fe and Al in the soil thereby blocking the sites which are mainly responsible for fixation of phosphorus in the soil (Juo and Fox, 1977;Subramanian and Kumaraswamy, 1989;Brouwere et al, 2003;Ghosal et al, 2011). Banik et al (2006) also showed that addition of organic manure markedly increased the availability of phosphorus in the soil. This increase in phosphorus availability in the soil was found to be statistically significant over control treatment and also over treatments with inorganic fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…The yield advantage on the application of organic sources is due to their capability to supply essential nutrients other than N, P and K. Application of farm yard manure is known to increase concentrations of Fe, Mn, Zn, and Cu in rice. Higher nutrients uptake with the application of inorganic fertilizer might be due to higher nutrient concentration along with higher biomass production [22,23]. Application of organic manure along with chemical fertilizer accelerates the microbial activity [24], increases nutrients use efficiency [25] and enhances the availability of the native nutrients to the plants resulting higher nutrients uptake [26].…”
Section: Discussionmentioning
confidence: 99%